Structural and superconducting properties of Y(Ba1-xKx)2Cu3O7-δ ceramics - Dihom, Mustafa Mousa; Shaari, Abdul Halim; Baqiah, Hussein; Al-Hada, Naif Mohammed; Talib, Zainal Abidin; Chen, Soo Kien; Azis, Rabaah Syahidah; Kechik, Mohd Mustafa Awang; Lim, Kean Pah; Abd-Shukor, Roslan (Elsevier, 2017)
Y(Ba1-xKx)2Cu3O7-δ ceramics (x = 0.00, 0.03, 0.05 and 0.08) were synthesized by thermal treatments of aqueous solution of metals nitrates and polyvinyl pyrrolidone (PVP) that acts as a capping agent. The effects of K-substitution on the crystal structure, microstructure and electrical resistance of samples were investigated. The X-ray diffractions results indicated an improvement of crystallinity and variation of lattice constant, a, b and c of YBa2Cu3O7-δ (Y123) phase with K-substitution. The K-substitution resulted in increasing of orthorhombicity factor compared to pure Y123. Microstructural observation using scanning electron microscopy showed that K-substitution promotes the grain growth of Y123. The superconducting transitions (Tc) of the substituted-samples were higher than that of the pure Y123. The Tc (onset) were 93, 97, 95, 95 K for the samples with x = 0.00, 0.03, 0.05 and 0.08, respectively. Comparing with pure sample, the substituted-samples showed sharper superconducting transition (ΔTc). The best superconducting properties was observed for sample with x = 0.03.